Critical Care Management of Acute-on-Chronic Liver Failure: Certainties and Unknowns - Reverter, Enric; Toapanta, David; Bassegoda, Octavi; Zapatero, Juliana; Fernandez, Javier (Seminars in Liver Disease, 2023)
Intensive care unit (ICU) admission is frequently required in patients with decompensated cirrhosis for organ support. This entity, known as acute-on-chronic liver failure (ACLF), is associated with high short-term mortality. ICU management of ACLF is complex, as these patients are prone to develop new organ failures and infectious or bleeding complications. Poor nutritional status, lack of effective liver support systems, and shortage of liver donors are also factors that contribute to increase their mortality. ICU therapy parallels that applied in the general ICU population in some complications but has differential characteristics in others. This review describes the current knowledge on critical care management of patients with ACLF including organ support, prognostic assessment, early liver transplantation, and futility rules. Certainties and knowledge gaps in this area are also discussed.
Keywords: prognosis; mortality; transplantation; liver support; infection